An assessment of correlation between fingerprint and malocclusion in a sample of Erbil city. - Bahoz Himdad Majeed; Omar Fawzi Chawshli (Erbil Dental Journal)
Abstract: Background and Objective: Dermatoglyphics has been shown to be useful in predicting orofacial abnormalities. The objective of this study was to explore if there is any link between fingerprints patterns and malocclusion type among a sample of Erbil city. Method: In this cross-sectional study, A total of 1000 finger prints were taken from 100 participants that were students, patients, and staffs of college of dentistry at Hawler Medical University. Age group was from 18 to 30. The fingerprints were recorded to analyze the type of pattern by digitalized finger scanner. Occlusion status was clinically assessed using Angle's classification of malocclusion. Results: The Angle's Class I malocclusion was the most common type of malocclusion among the study participants, according to the data in this study. The most predominant fingerprint was loop pattern and the least pattern was arch. All three types of fingerprints were mostly found in participants with Angle’s Class I malocclusion. There was no significant difference between types of finger print patterns in all ten hand fingers and malocclusions. Conclusion: in all 10 fingers of both hands, there was no correlation between any patterns of fingerprints and malocclusions.